The Need for PGY2‐Trained Clinical Pharmacy Specialists. Issue 6 (18th April 2014) - Ragucci, Kelly R.; O'Bryant, Cindy L.; Campbell, Kristin Bova; Buck, Marcia L.; Dager, William E.; Donovan, Jennifer L.; Emerson, Kayleigh; Gubbins, Paul O.; Haight, Robert J.; Jackevicius, Cynthia; Murphy, John E.; Prohaska, Emily
<x xml:space="preserve">Abstract</x> The American College of Clinical Pharmacy and other stakeholder organizations seek to advance clinical pharmacist practitioners, educators, and researchers. Unfortunately, there remains an inadequate supply of residency‐trained clinical specialists to meet the needs of our health care system, and nonspecialists often are called on to fill open specialist positions. The impact of clinical pharmacy specialists on pharmacotherapy outcomes in both acute care and primary care settings demonstrates the value of these specialists. This commentary articulates the need for postgraduate year two (PGY2)‐trained clinical specialists within the health care system by discussing various clinical and policy rationales, interprofessional support, economic justifications, and their impact on quality of care and drug safety. The integrated practice model that has grown out of the American Society of Health‐System Pharmacists Pharmacy Practice Model Initiative (PPMI) could threaten the growth and development of future clinical specialists. Therefore, the ways in which PGY2‐trained clinical pharmacist specialists are deployed in the PPMI require further consideration. PGY2 residencies provide education and training opportunities that cannot be achieved in traditional professional degree programs or postgraduate year one residencies. These specialists are needed to provide direct patient care to complex patient populations and to educate and train pharmacy students and postgraduate residents. Limitations to training and hiring PGY2‐trained clinical pharmacy specialists include site capacity limitations and lack of funding. A gap analysis is needed to define the extent of the mismatch between the demand for specialists by health care systems and educational institutions versus the capacity to train clinical pharmacists at the specialty level.